Accuracy of Targeting Under the Rural Employment Guarantee Programme: A Comparison Between West Bengal and Rest of India. (12th October 2018) - Das, Upasak
Abstract: One major success indicator of any welfare programme is accuracy of targeting of the benefits to the intended population. Using data from 2009–2010 and 2011–2012, this paper assesses targeting in terms of participation of the poorer households in Mahatma Gandhi National Rural Employment Guarantee Act in the Indian state of West Bengal and compares it with rest of the country. Although implementation of the programme in the state has been poor, the targeting performance is found to be fair in comparison to other parts. The findings lay emphasis on improvement in other dimensions of the programme to realise the optimal benefits. © 2018 John Wiley & Sons, Ltd.